What would Socrates do? An exploratory study of methods, materials and pedagogies in high school philosophy - Laura Elizabeth Pinto; Dwight Boyd; Graham P. McDonough (University of Windsor, 2009)
For over half a century, North American philosophers and teachers have been interested in introducing philosophy courses at the high school level. In 1995, such a course was introduced into the curriculum for the Canadian province of Ontario, making it the first and only English-speaking jurisdiction in North America to have philosophy as part of its official curriculum, yet to date no investigation of how these courses are taught exists. Our research addresses this gap in the literature by describing the results of the exploratory stage of our empirical investigation into the practices of Ontario high school philosophy teachers. A survey reveals that they tend to rely heavily on textbooks and employ a wide range of pedagogies in their philosophy classes, favouring discussion and lecture, despite mixed perceptions about their effectiveness.